(untitled) (Journal of Environmental Science and Natural Resources, 2021)
Pesticide residues in vegetables have become a major concern associated with food safety issues. Five types of winter vegetables like bean, brinjal, tomato, cauliflower and cabbage were collected from six markets of Rajshahi District during January, , 2019 in Bangladesh. Residues of commonly used pesticides (Acephate, Dimethoate, Diazinon, Fenotrothion, Malathion, Chlorpyrifos and Quinalphos) in winter vegetable samples were determined using Gas Chromatography-Flame Thermionic Detector (GC-FTD) procedures. A quick, easy, cheap, effective, rugged and safe (QuEChERS) method with acetate buffering (AOAC Official Method 2007.01) was used for sample preparation. Out of 30 samples, pesticide residues were found only in one brinjal and two tomato samples. The result showed that tomato samples collected from Shaheb bazar and Kharkhari bazar of Rajshahi City contained 0.047 mg/kg and 0.139 mg/kg dimethoate residue, respectively. Brinjal sample collected from Shalbagan bazar, Rajshahi, contained 0.052 mg/kg dimethoate residues. The detected pesticide residue dimethoate of these three samples was higher than maximum residue level (0.01 mg/kg). Environ. Sci. & Natural Resources, 12(1&2): 43-50, 2019